Maker-centricity and 'edge-places of creativity': CARE-full making in a CARE-less world. (December 2022) - Hackney, Fiona; Onions, Laura; Rogers, Gavin; Figueiredo, Deirdre; Loveday, Mary
Susan Luckman, citing Katherine Gibson's call for a return to 'the grass-roots work of engaging the community and being open to developing new economies', advocates a vision of creative industries that builds the affordances of 'edge-places of creativity'. Luckman's focus is non-urban localities. Her proposal, nevertheless, could equally apply to the amateur craft groups, community organisations and independent businesspeople that the Arts and Humanities Research Council–funded projects Co-Producing CARE: Community Asset-based Research and Enterprise, and Maker-Centric: Building Place-based, Co-making Communities worked with in deprived inner-city areas in the British Midlands. Both projects were undertaken with Craftspace and other stakeholder organisations, worked collaboratively with community groups, employed co-production processes and combined hand-making with digital fabrication. The aim of each project was to prototype a method with communities that builds agencies (cultural, social, economic, skills-based) through making and could be applied by other groups. While the CARE method was concerned with the affordances of collaborative making, Maker-Centric looked at these through a heritage and placed-based lens. This article examines the potential for local, collaborative, purposeful, social making as an 'edge-place' activity for creative enterprise that is inclusive and supportive.